2021
DOI: 10.1063/5.0046373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time delay in a bistable synthetic gene network

Abstract: The essence of logical stochastic resonance is the dynamic manipulation of potential wells. The effect of time delay on the depth of potential wells and the width of a bistable region can be inferred by logic operations in the bistable system with time delay. In a time-delayed synthetic gene network, time delay in the synthesis process can increase the depth of the potential wells, while that in the degradation process, it can reduce the depth of the potential wells, which will result in a decrease in the widt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…In addition, it has been demonstrated that correlated internal and external noises [21][22][23] can also produce logic operations in bistable systems. It has also been shown that other elements can produce logic operations in bistable systems, including system parameters, [24] time delay, [25][26][27] coupling between two subsystems, [28] and periodic and non-periodic forces. [29][30][31] Since three different inputs correspond to two outputs in a bistable system this may cause information to be lost, making XOR logic unattainable.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been demonstrated that correlated internal and external noises [21][22][23] can also produce logic operations in bistable systems. It has also been shown that other elements can produce logic operations in bistable systems, including system parameters, [24] time delay, [25][26][27] coupling between two subsystems, [28] and periodic and non-periodic forces. [29][30][31] Since three different inputs correspond to two outputs in a bistable system this may cause information to be lost, making XOR logic unattainable.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Noise is not the only factor to induce logical resonance. Periodic force, [20][21][22][23] parameter, [24] time delay, [25][26][27] autapse, [28] coupling, [29,30] and chaotic signal [31,32] can be used as replacements for stochastic noise to obtain similar results with SR. The scope of the research has been extended from typical bistable systems to multi-stable systems in order to explore all types of logical operations.…”
Section: Introductionmentioning
confidence: 99%
“…[27] On the other hand, some researchers have carried out LSR-related studies from a theoretical perspective, and confirmed that stochastic noise is not necessary for logical resonance. Many deterministic factors, such as periodic force, [34][35][36][37][38] time delay, [39][40][41][42][43] parameters, [44,45] coupling, [46][47][48] and temperature, [49] can also induce LSR-like phenomena.…”
Section: Introductionmentioning
confidence: 99%